The Influence of Workplace Environment, Work Discipline, and Financial Compensation on Employee Performance at PT BPR Naga Batubulan - Wirastini, Ni Nyoman Ayu Tri; Sariani, Ni Ketut (Formosa Journal of Applied Sciences, 2024)
This study aims to evaluate the impact of workplace environment, work discipline, and financial compensation on employee performance at PT BPR Naga Batubulan. Employing a saturated sampling technique, 40 employees were selected as respondents and analyzed using multiple linear regression analysis. Results reveal significant and positive effects of the workplace environment, work discipline, and financial compensation on employee performance. The study underscores the importance of these factors in enhancing overall productivity, job satisfaction within the organization. By recognizing the significance of a conducive work environment, effective work discipline, and fair financial compensation, companies can better strategize for employee retention and performance improvement. This research provides valuable insights for HR practitioners and organizational leaders aiming to optimize workforce effectiveness and morale.